A házassági javak megjelenése a Corpus Iuris Canoniciben - Völgyesi, Levente (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
For a long time, the regulation of marriage law in a unified system was not realized. In the late Middle Ages, canon law regulated the most important elements of marriage in systematic collections. The goods of the marriage were primarily contained in the Decretum Gratiani and the Liber extra. These goods were: fidelity, indissolubility, birth and care of children, sacramental character. Marriage law had four layers: ius naturalis, Holy Scripture, Roman law and canon law. Later, there was a unified regulation both in the field of Catholic dogmatics and canon law (Catechism (1566, 1992) and Corpus Iuris Canonici (1917, 1983).